Correlation of T follicular helper cells and plasmablasts with the development of organ involvement in patients with IgG4-related disease. (14th December 2017) - Kubo, Satoshi; Nakayamada, Shingo; Zhao, Jidong; Yoshikawa, Maiko; Miyazaki, Yusuke; Nawata, Aya; Hirata, Shintaro; Nakano, Kazuhisa; Saito, Kazuyoshi; Tanaka, Yoshiya
Abstract: Objective: To assess the role of an abnormal immune network in the pathology of IgG4-related disease (IgG4-RD). Methods: Sixteen patients diagnosed with IgG4-RD at our institution were selected. Peripheral immunocompetent cells were immunophenotyped by multicolour flow cytometry to assess the association between clinical manifestation and pathological findings. Results: Compared with healthy controls, IgG4-RD patients showed comparable proportions of Th1 and Th17 cells, but higher proportions of Treg and follicular helper T (Tfh) cells. Further, the proportions of class-switched memory B cells and plasmablasts were higher in patients. Among all phenotypes, in particular, the plasmablast proportion increased from 4.2% (controls) to 16.5% (patients). The serum IgG levels were found to be correlated with the proportions of plasmablasts and Tfh cells, but not with those of other T cell subsets. In patients with extraglandular symptoms, only plasmablasts, Tfh cells and memory Treg cells were increased. Histopathological examination revealed a marked Tfh (CD4 + Bcl6 + ) cell infiltration; the increase of Tfh cells in the peripheral blood thus reflected the degree of Tfh cell infiltration into the tissue. Although steroid therapy reduced plasmablast and Tfh cell proportions, the memory Treg cell proportion remained unchanged. Conclusion: The association found between Tfh cells and plasmablasts, linked with biological plausibility, suggests that Tfh cells contribute to the pathogenesis of IgG4-RD. Our results also suggested that controlling the Tfh cell–plasmablast axis could be a novel therapeutic strategy for treating IgG4-RD.